A NEW WAY TO SOLVE BASIC EDUCATION PROBLEMS IN INDONESIA IN ADAPTING TO MULTICULTURALISM - Yuyun Elizabeth Patras; Rais Hidayat; Edwita Edwita; Zulela M. S.; Gusti Yarmi (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2022)
This study has the aim of describing the results of research on multiculturalism in Indonesia. The findings of the research papers will be used as the basis for finding new ways, especially for the implementation of multicultural education in the context of basic education that can be used to solve problems in education. The research method used a content analysis of 12 articles in English from 2018-2022 using the keyword "multicultural Indonesia". Research findings indicate that teachers in primary education need to adapt to multicultural developments in Indonesia to solve educational problems. New ways for teachers to promote multiculturalism include: increasing philosophical and sociological understanding of Indonesia; strengthening understanding of policies and curriculum, as well as increasing learning (pedagogy) with a multicultural orientation in the Indonesian context. The recommendation from this research is to apply the multicultural learning model in the primary education classroom.